As redes sociais virtuais (RSV) como estratégia de sustentação dos empreendimentos de Manaus e Rio Preto da Eva, Amazonas, durante a pandemia de SARS-CoV-2 - Curitiba, Jhenyffer de Souza (Brasil, 2022)
The sars-cov-2 pandemic has motivated a significant number of entrepreneurs and retailers to use digital sales platforms to keep their businesses in operation. The present study aimed to identify how Virtual Social Networks (RSV) were used by entrepreneurs in the cities of Manaus and Rio Preto da Eva, in the State of Amazonas, during the sars-cov-2 pandemic. The central hypothesis is that RSV was used as a business support strategy, aiming to refrain the volume of